2018
DOI: 10.2174/1567205015666180702105740
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Alleviates Amyloid-Beta Pathology in the Brain of APP/PS1 Transgenic Mice via Inhibiting β/γ-Secretases Activity and Enhancing α-Secretases

Abstract: BBR inhibits the activity of β/γ-secretases, enhances α-secretases, and lowers the Aβ level in the hippocampus of AD mice, and improves Alzheimer's-like cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 0 publications
2
42
0
Order By: Relevance
“…BACE-1 is the major β-secretase that determines Aβ production. This result is consistent with the animal experiment of Cai [103] in male APP/ PS1 transgenic mice. Zhu found that BBR inhibited the expression of BACE by activating the ERK1/2 pathway in HEK293 cells, reducing the production of Aβ40/42 [104].…”
Section: Berberinesupporting
confidence: 92%
“…BACE-1 is the major β-secretase that determines Aβ production. This result is consistent with the animal experiment of Cai [103] in male APP/ PS1 transgenic mice. Zhu found that BBR inhibited the expression of BACE by activating the ERK1/2 pathway in HEK293 cells, reducing the production of Aβ40/42 [104].…”
Section: Berberinesupporting
confidence: 92%
“…α -, β -, and γ -secretases are considered to be the main enzymes that cause proteolytic cleavage of APP and produce A β peptides [810]. Accumulative evidence implicated that A β secretion resulted from α - and β -secretase cleavage of APP, respectively, to induce sAPP- α and sAPP- β [7, 11, 12]. However, sAPP- α has low expression and derives from the nonamyloidogenic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, numerous BACE1 inhibitors have been tested in clinical trials. The administration of BACE1 inhibitor could dramatically decrease the A β level and attenuate behavioral deficits in APP transgenic mice [12, 19], yet their brains naturally possess high concentrations of soluble A β . The deletion of BACE1 gene decreased A β secretion and improved learning and memory in AD mouse models [20].…”
Section: Introductionmentioning
confidence: 99%
“…AChE can also have noncholinergic effect, i.e., inducing Aβ oligomerization via the PAS active site (TRP 279 ), or regulating inflammation by CAP. The main alkaloids in STR, CR, and PCC could alleviate Aβ-induced injury or have an antineuroinflammatory effect [12,47,48]. The alkaloids in STR, CR, and PCC can affect other factors related with AD: fangchinoline has a protective effect on cyanide-induced neurotoxicity [49,50]; coptisine ameliorates cognitive impairment by inhibiting indoleamine 2,3-dioxygenase [51]; and berberine shows multiple activities to relieve symptoms of AD [52].…”
Section: Discussionmentioning
confidence: 99%